1986
DOI: 10.1161/01.cir.74.3.463
|View full text |Cite
|
Sign up to set email alerts
|

Septal geometry in the unloaded living human heart.

Abstract: Right ventricular loading leads to diastolic septal flattening in man without necessarily requiring right ventricular pressure to exceed left ventricular pressure. This observation suggested that the unstressed septal configuration is flat and that its normal concave shape is due to the left-to-right transseptal pressure gradient. To examine this hypothesis, we studied septal configuration by twodimensional echocardiography in nine patients with normal global and regional left ventricular function during surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 17 publications
1
15
1
Order By: Relevance
“…The septal contribution differs from patients with volume loaded rV such as patients with pulmonary regurgitation or atrial septal defects where the septum moves towards the right side in systole [11,13,25,26]. The movement of septum towards the left in our study is in concordance with earlier studies with pressure loaded rV [16,[27][28][29]. SV long% was decreased on the left side in patients with PH compared to controls, but did not differ on the right side between patients and controls (Table 3; Fig.…”
Section: Resultssupporting
confidence: 89%
“…The septal contribution differs from patients with volume loaded rV such as patients with pulmonary regurgitation or atrial septal defects where the septum moves towards the right side in systole [11,13,25,26]. The movement of septum towards the left in our study is in concordance with earlier studies with pressure loaded rV [16,[27][28][29]. SV long% was decreased on the left side in patients with PH compared to controls, but did not differ on the right side between patients and controls (Table 3; Fig.…”
Section: Resultssupporting
confidence: 89%
“…These results are similar to those we previously reported1' in experiments during pulmonary artery constriction, are similar to the studies of others, 3,20,2' and are in general agreement with our current understanding of diastolic septal mechanics. [25][26][27] The importance of the contribution of pericardial constraint to the mechanism of the shift has been emphasized previously; opening the pericardium results in less septal shift than occurs while the pericardium is intact.1 7} 28 Our data differ from those in a recent report that concluded that septal shift was not an important factor in the reduction of LV volume in dogs with pulmonary vascular injury induced by glass beads." The degree of elevation of RV diastolic pressure in that study suggests that a septal shift was not observed because the increase in RV afterload was not as great as that produced by the repeated embolization in our study.…”
Section: Transseptal Pressure Gradientcontrasting
confidence: 50%
“…3) is generally considered a noninvasive reference standard for evaluating biventricular dimensions, geometry and function [40,41]. The configuration and curvature of the septum is a function of transseptal pressure gradient [42,43], whereas transmural pressure gradient determines the left ventricular free wall curvature [44]. Patients with PH may have a substantially reduced trans-septal pressure gradient, which may lead to the frequently observed flattening (or bowing) of the intraventricular septum (IVS) [42].…”
Section: Cardiac Magnetic Resonancementioning
confidence: 99%